The Carbonic Anhydrase Inhibitor Ethoxzolamide Inhibits the Mycobacterium tuberculosis PhoPR Regulon and Esx-1 Secretion and Attenuates Virulence - Johnson, Benjamin K. (Antimicrob Agents Chemother, 2015)
Mycobacterium tuberculosis must sense and adapt to host environmental cues to establish and maintain an infection. The two-component regulatory system PhoPR plays a central role in sensing and responding to acidic pH within the macrophage and is required for M. tuberculosis intracellular replication and growth in vivo. Therefore, the isolation of compounds that inhibit PhoPR-dependent adaptation may identify new antivirulence therapies to treat tuberculosis. Here, we report that the carbonic anhydrase inhibitor ethoxzolamide inhibits the PhoPR regulon and reduces pathogen virulence. We show that treatment of M. tuberculosis with ethoxzolamide recapitulates phoPR mutant phenotypes, including downregulation of the core PhoPR regulon, altered accumulation of virulence-associated lipids, and inhibition of Esx-1 protein secretion. Quantitative single-cell imaging of a PhoPR-dependent fluorescent reporter strain demonstrates that ethoxzolamide inhibits PhoPR-regulated genes in infected macrophages and mouse lungs. Moreover, ethoxzolamide reduces M. tuberculosis growth in both macrophages and infected mice. Ethoxzolamide inhibits M. tuberculosis carbonic anhydrase activity, supporting a previously unrecognized link between carbonic anhydrase activity and PhoPR signaling. We propose that ethoxzolamide may be pursued as a new class of antivirulence therapy that functions by modulating expression of the PhoPR regulon and Esx-1-dependent virulence.